Effects of differential reinforcement of choosing phrases about reading upon the duration of reading behavior - Faleiros, Thais Cazati; Hübner, Maria Martha Costa (Revista Brasileira de Terapia Comportamental e Cognitiva, 2007)
In the scope of studies that investigate the effects of manipulation in verbal antecedents upon the related non verbal behavior, the present study evaluated the effect of differential reinforcement of one response class (choice of phrases about positive aspects about reading, interpreted as tacts with positive qualifying autoclitics) upon other class (the choice of reading behavior), reinforcing choices of phrases about positive aspects of reading and observing its effects upon the emission of reading behavior. It were registered activities and photographs chosen before and after the training. During training, four phrases appeared in a computer screen and just the choice of one of them (related to reading) was reinforced with points. The results indicated an augment of the choices in reading behavior as well as in the time of reading for the majority of the participants and an augment of the choices of choosing photographs related to reading, when compared to the results of the baseline. The results are interpreted according to behavior verbally governed.